Pengaruh Model Pembelajaran Mordiscvein Terhadap Motivasi Belajar Siswa Sekolah Dasar Pada Materi Perubahan Wujud Benda - Meylan Saleh; Widi Candika Pakaya (JURUSAN PENDIDIKAN GURU SEKOLAH DASAR, 2025)
The research problem addressed in this study is whether the Mordiscvein learning model has a significant effect on elementary school students’ learning motivation in the topic of changes in the states of matter. The purpose of this study is to determine the effect of the Mordiscvein learning model on students’ learning motivation in elementary schools on the topic of changes in the states of matter. This study employed a quantitative research approach to examine the effect of the Mordiscvein learning model on elementary school students’ learning motivation. The research design used was a true experimental design, specifically a two-group pretest–posttest design. The population of this study consisted of all fourth-grade students in the elementary school, totaling 25 students. Data were collected through observation. Based on the results of the SPSS version 23.0 analysis using the independent samples t-test for equality of means, the calculated t-value was 3.655, which was greater than the t-table value of 1.677, and the significance value was 0.001, which was lower than the significance level of α = 0.05. Therefore, H₀ was rejected and H₁ was accepted. It can be concluded that the use of the Mordiscvein learning model has a significant effect on students’ learning motivation in science subjects for fourth-grade students at SDN 57 Kota Timur, Gorontalo City.